2004
DOI: 10.1542/peds.114.2.e160
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Secondary Diagnoses for Infants Born With Hypoplastic Left Heart Syndrome

Abstract: ABSTRACT. Objective. To explore clinical outcomes and secondary diagnoses present at discharge for infants born with hypoplastic left heart syndrome (HLHS), from a national perspective.Methods. We examined hospitalizations for infants <30 days of age who were born with HLHS, using hospital discharge data from the 1997 Kids Inpatient Database. To explore treatment choices, clinical outcomes, and resource use, we used International Classification of Diseases, 9th Revision, Clinical Modification diagnostic and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…The sample is drawn from a federally funded hospital discharge data set, which has previously been used to describe hospitalized pediatric patients and to identify variations in their care. 18,[20][21][22] Our objective is to describe the characteristics of hospital admissions of adolescents who attempted suicide and the patterns of discharge disposition, and specifically to test the hypothesis that disposition varies as a function of hospital type and geographic region.…”
Section: Arch Pediatr Adolescmentioning
confidence: 99%
“…The sample is drawn from a federally funded hospital discharge data set, which has previously been used to describe hospitalized pediatric patients and to identify variations in their care. 18,[20][21][22] Our objective is to describe the characteristics of hospital admissions of adolescents who attempted suicide and the patterns of discharge disposition, and specifically to test the hypothesis that disposition varies as a function of hospital type and geographic region.…”
Section: Arch Pediatr Adolescmentioning
confidence: 99%
“…Potentially lethal congenital lesions with a high risk for mortality may be detected as early as 16 weeks gestation (1)(2)(3)(4). Routine prenatal screening has led to a reduction in the frequency of live births of infants with significant congenital defects such as hypoplastic left heart syndrome (HLHS), partly as a result of planned termination of pregnancy (5). However, alternatives to pregnancy termination, including neonatal surgical palliation or heart transplantation, (2) continue to offer improving outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of national data of 550 children with HLHS noted a 32% mortality rate for the Norwood procedure (Connor, Arons, Figueroa, & Geddie, 2004). Another study reported a much lower mortality rate of 8% (Sano, Huang, Kasahara, Yoshizumi, Kotani, & Ishino, 2009).…”
Section: Treatment Optionsmentioning
confidence: 98%
“…Mortality rates for the Glenn and Fontan are much lower, at 2 to 5.4% and less than 5% respectively (Connor, et al, 2004). Although surgical survival rates have improved greatly in the past 20 years, there is still a high possibility that children with HLHS are at risk for mental and physical abnormalities (Connor & Thiagarajan, 2007).…”
Section: Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation